Food Allergy a Constant Concern to the Medical World and Healthcare Providers: Practical Aspects - Lucia M. Sur; Ionel Armat; Emanuela Duca; Genel Sur; Iulia Lupan; Daniel Sur; Gabriel Samasca; Cecilia Lazea; Calin Lazar (Life, 2021)
Food allergy (FA) is a condition with a growing incidence and is a constant concern for the medical world and healthcare providers. With potential symptoms including anaphylaxis, in the event of an allergic reaction the patient’s life may well be endangered. The diagnosis of FA is a continuous challenge because mild cases tend to be ignored or diagnosed late and young children with allergies are cared for by parents, who are not always able to accurately interpret symptoms. It is very important to be able to differentiate FAs from food intolerance and toxic reactions to food. An accurate diagnosis is required to provide personalized management of an FA. More sophisticated and accurate diagnostic tests, including component diagnosis and epitope reactivity, allow the provision of a directed diagnosis, a more accurate therapeutic approach, and a useful prognostic evaluation. Tests used in current practice include the specific search for serum IgE, elimination diets, oral food challenges, single, blind, and double-blind (DBPCFC) tests, as well as skin tests. The risk of anaphylaxis can be assessed by molecular diagnostics/component-resolved diagnosis (CRD) and by conducting a basophilic activation test (BAT). These tests allow a planned, personalized treatment based on molecular and clinical profiles. CRD can determine the individual profile of allergic molecular reactivity and enable the formulation of a prognostic judgment. Our article highlights the importance of knowing the immune mechanisms, diagnostics, and immunotherapies in FAs. Starting from observing exposure to food allergens, to identifying allergic reactions, analysing the severity of clinical manifestations, noting the possibilities of diagnosis, and illustrating adequate management strategies.